TODA-YAMAMOTO CAUSALITY TEST BETWEEN MONEY MARKET INTEREST RATE AND EXPECTED INFLATION: THE FISHER HYPOTHESIS REVISITED - Santos R. Alimi; Chris C. Ofonyelu (European Scientific Journal, ESJ, 2013)
﻿﻿﻿This paper investigates the relationship between expected inflation and nominal interest rates in Nigeria and the extent to which the Fisher effect hypothesis holds, for the period 1970-2011. We made attempt to advance the field by testing the traditional closed-economy Fisher hypothesis and an augmented Fisher hypothesis by incorporating the foreign interest rate and nominal effective exchange rate variable in the context of a small open developing economy, like Nigeria. We used Johansen cointegration approach, error correction model and the Toda and Yamamoto (1995) causality testing method. This study found: (i) that money market interest rates and expected inflation move together in the long run but not on one-to-one basis. This indicates that full Fisher hypothesis does not hold but there is a strong Fisher effect in the case of Nigeria over the period under study (ii) consistency with the international Fisher hypothesis, these domestic variables have a long run relationship with the international variables (iii) that in the closed-economy context, the causality run strictly from expected inflation to nominal interest rates as suggested by the Fisher hypothesis and there is no “reverse causation.” But in the open economy context, the expected inflation and international variables contain the information that predict the nominal interest rate (iv) finally that only about 22 percent of the disequilibrium between long term and short term interest rate is corrected within the year.